Case Report: Abdominal surgery with the support of Impella (SURGELLA), a new frontier to be explored - Guarracini, Stefano; Di Sebastiano, Pierluigi; Di Mola, Fabio Francesco; Di Renzo, Raffaella; Mazzocchetti, Lorenzo; Calafiore, Antonio M.; Di Mauro, Michele (Frontiers in Cardiovascular Medicine, 2024)
A 74-year-old man with advanced heart failure was admitted to the hospital with a diagnosis of colorectal cancer, and he underwent surgery. To maintain stable hemodynamics, the Impella CP device was used. The patient was weaned from the device shortly after surgery, and he had an uneventful postoperative course. This case may pave the way for non-procrastinating surgery in patients with poorly stable hemodynamics.